Psychology why it matters - Wiseman, Richard (Richard John) 1966- (Why it matters (Polity Press), 2022)
"Richard Wiseman takes you on a personal journey into this fascinating world, focusing on what makes for meaningful research. He explores how psychology reveals the hidden workings of the mind, boosts critical thinking, debunks myths, improves lives, and informs debates in politics, philosophy, and education. This insider's guide lifts the lid on how psychologists go about their work, examines contemporary challenges associated with studying the mind, and encourages students and researchers to reflect on why they do what they do. If you've ever wanted to think like a psychologist, spot a liar, uncover the truth about happiness, or discover how to create a more altruistic society, then this book is for you."-- Back cover.